2020
DOI: 10.2139/ssrn.3597996
|View full text |Cite
|
Sign up to set email alerts
|

All that Glitters Is not Gold. Effects of Working from Home on Income Inequality at the Time of COVID-19

Abstract: All that glitters is not gold. Effects of working from home on income inequality at the time of COVID-19 GLO Discussion Paper, No. 541

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 38 publications
0
11
0
1
Order By: Relevance
“…With respect to the literature, these results may shed light on the evidence provided in studies such as by Bonacini, Gallo, and Scicchitano (2020) who have shown that working from home (due to social distancing) increases income inequality among employees, potentially due to the heterogeneity across education levels. This is also consistent with the idea that lower-income people have to continue working outside during COVID-19, as they have experienced higher unemployment rates as shown in studies such as by Cho and Winters (2020).…”
Section: Education Groupsmentioning
confidence: 62%
“…With respect to the literature, these results may shed light on the evidence provided in studies such as by Bonacini, Gallo, and Scicchitano (2020) who have shown that working from home (due to social distancing) increases income inequality among employees, potentially due to the heterogeneity across education levels. This is also consistent with the idea that lower-income people have to continue working outside during COVID-19, as they have experienced higher unemployment rates as shown in studies such as by Cho and Winters (2020).…”
Section: Education Groupsmentioning
confidence: 62%
“…With respect to the literature, these results may shed light on the evidence provided in studies such as by Bonacini, Gallo, and Scicchitano (2020) who have shown that working from home (due to social distancing) increases income inequality among employees, potentially due to the heterogeneity across education levels. This is also consistent with the idea that lowerincome people have to continue working outside during COVID-19, as they have experienced higher unemployment rates as shown in studies such as by Cho and Winters (2020).…”
Section: Education Groupsmentioning
confidence: 62%
“…The COVID-19 emergency created concern in many people who were reporting anxiety, depression and stress, especially when they were already suffering from poor health [5,6]. Studies on work at the time of COVID-19 also show that confinement has led to an increase in inequalities between groups of employees, with some employees more satisfied and others more dissatisfied with their work [7] and, in the long term, might also lead to an increase in wage inequality among Italian employees [8]. On the other hand, remote working has also allowed employees to discover they could work from home [9].…”
Section: Introductionmentioning
confidence: 99%